Focused Cardiac Ultrasonography: Current Applications and Future Directions. (26th August 2018) - Luong, Christina L.; Ong, Kevin; Kaila, Kendeep; Pellikka, Patricia A.; Gin, Kenneth; Tsang, Teresa S. M.
Abstract : Focused cardiac ultrasonography is performed by clinicians at the bedside and is used in time‐sensitive scenarios to evaluate a patient's cardiovascular status when comprehensive echocardiography is not immediately available. This simplified cardiac ultrasonography is often performed by noncardiologists using small, portable devices to augment the physical examination, triage patients, and direct management in both critical care and outpatient settings. However, as the use of focused cardiac ultrasonography continues to expand, careful consideration is required regarding training, scope of practice, impact on patient outcomes, and medicolegal implications. In this review, we examine some of the challenges with rapid uptake of this technique and explore the benefits and potential risk of focused cardiac ultrasonography. We propose possible mechanisms for cross‐specialty collaboration, quality improvement, and oversight.